CYBER COMMUNICATIVE ADDICTION IN THE STRUCTURE OF MODERN DIGITAL ADDICTIONS: A THEORETICAL REVIEW (Psychology Travelogs, 2025)
The rapid expansion of digital technologies and the widespread use of social media have significantly transformed modern patterns of interpersonal communication, self-presentation, and socialization. These changes have contributed to the emergence of new forms of addictive behavior, among which cyber-communicative addiction is becoming one of the most prevalent and socially significant types. This phenomenon is especially acute among young people, for whom online platforms serve not only as a means of communication but also as a space for identity construction, emotional regulation, and compensation for unmet social needs. Cyber-communicative addiction manifests itself through a compulsive need for constant online interaction, dependence on social approval, and emotional reinforcement, ultimately reducing the quality of offline relationships, impairing emotional self-regulation, increasing anxiety, and distorting self-perception.A review of international and Ukrainian research shows substantial scientific interest in digital addictions, especially Internet addiction, examined by I. Goldberg, K. Young, M. Griffiths, J. Suler and others. Ukrainian scholars such as T. Bolbot, T. Vakulich, T. Karabin, and L. Yurieva explore diagnostic, preventive, and corrective aspects of this issue. Despite notable progress, the mechanisms underlying cyber-communicicative addiction in student populations remain insufficiently studied, necessitating further theoretical modeling and empirical research.The aim of the article is to systematize current theoretical approaches to understanding cyber-communicative addiction within the broader structure of digital addictions, to clarify its psychological characteristics, and to outline its mechanisms of formation. The analysis highlights the role of cognitive-behavioral and socio-psychological factors, including loneliness, low self-esteem, emotional instability, and deficits in self-regulation. Special attention is paid to the compensatory function of online communication, algorithmic reinforcement through social media feedback, and the risks associated with replacing authentic interpersonal contacts with virtual interactions.
Keywords: cybercommunicative addiction; social networks; internet addiction; digital addictions; university stu; dents; psychological factors